Socioeconomic and Environmental Impacts of Tobacco Farming in Khyber Pakhtunkhwa, Pakistan: Impact of Tobacco Farming in Pakistan - Qurat-ul-ain Altaf; Abid Hussain; Bilal Khan Yousafzai (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Tobacco production and curing cause a threat to the environment through injudicious use of pesticides, imbalanced use of chemical fertilizers, and excessive consumption of local firewood. Keeping all this in retrospect, this study has been designed to assess the impact of tobacco farming on family workers, and witness on spot involvement of children and nursing/ expecting mothers in tobacco-related health-hazardous tasks. General objective of the study is to document both the positive and negative environmental and socioeconomic externalities of tobacco production in the study area. It is based both on primary data and secondary statistics. Primary data has been collected from sixty farmers for the tobacco season 2021; including forty contract and twenty non-contract sample farmers. Farmers conceive that tobacco farming has a bad impact on human health (93 %), and causes degenerative deforestation and resource depletion (68 % each). Use of Green Tobacco Sickness gloves and Personal Precautionary Equipment was reported by eighty and sixty-two percent of the farmers, respectively. Impact of the disease on the workers’ health was reported by thirty-five percent of contracted farmers, and 90 percent of non-contracted ones. Thus, the impact of the disease on human health was severe on non-contracted farms, mainly due to little or no use of Personal Precautionary Equipment. Cost of Personal Precautionary Equipment per season at the contracted farms was much higher (US$ 18.0) than at non-contracted ones (US$ 2.0). While the treatment cost of Green Tobacco Sickness or other agrochemical-related diseases of contracted farming households was 2.5 times lower than non-contracted ones. As per the results of the double log Ordinary Least Squares regression model about medical treatment cost, the coefficient of age of household head and use of Personal Precautionary Equipment have negative expected signs and are statistically significant. Laboratory tests of soil and water samples have revealed hazardous levels of Sodium Chloride and Dissolved Oxygen in canal water, which indicate imbalanced use of fertilizers by the growers and leaching of excessive nutrients below the root zone. Tobacco companies’ contracted growers were found to have less occupational health hazards. Thus, raising awareness among tobacco growers about the importance of adopting precautionary measures and use of Personal Precautionary Equipment can reduce the negative effects of tobacco farming.